1991
DOI: 10.1136/gut.32.2.196
|View full text |Cite
|
Sign up to set email alerts
|

Binding of kidney bean (Phaseolus vulgaris) isolectins to differentiated human colon carcinoma Caco-2 cells and their effect on cellular metabolism.

Abstract: The binding of Phaseolus vulgaris (PHA) isolectins L4 and E4 Both isolectins stimulated the incorporation of thymidine and glucosamine, but neither PHA-L4 nor PHA-E4 were able to influence the incorporation of uridine. With respect to fucose, methionine, and N-acetyl mannosamine, the stimulatory effect remained confined to PHA-E4. Since PHA-L4 and PHA-E4 were tested at the same concentrations, PHA-E4 is more effective than PHA-L4. The changes in the uptake of radioactive precursors were lost after heat ina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 22 publications
(5 reference statements)
0
8
0
Order By: Relevance
“…This is thought to be due to malabsorption of nutrients since distortion of intestinal architecture and loss of brush border enzymes [11,16,20,21] have been seen. These reports followed a relatively long duration of exposure in weeks or months.…”
Section: Sucrose Reduced Legume Lectin-induced Weight Lossmentioning
confidence: 97%
“…This is thought to be due to malabsorption of nutrients since distortion of intestinal architecture and loss of brush border enzymes [11,16,20,21] have been seen. These reports followed a relatively long duration of exposure in weeks or months.…”
Section: Sucrose Reduced Legume Lectin-induced Weight Lossmentioning
confidence: 97%
“…Previous studies revealed that the growth-promoting effects of PHA resulted from specific binding to carbohydrates on the cell surface [10]. N-acetyl- D -galactosamine had been shown to specifically inhibit hemagglutination and leukoagglutination by PHA without destroying either the cells or the PHA [35].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, lectins stimulate proliferation in the large intestine and the pancreas [7, 8]. At the cellular level, binding and endocytosis of PHA by epithelial cells increased DNA and RNA contents [9, 10]and stimulated cellular protein synthesis [11], but the underlying mechanisms are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…A multiplicity of infection (moi) of 100-400 bacteria per Caco-2 cell was used. Caco-2 cells were routinely grown as described previously (Hendriks et al, 1991).…”
Section: Bacterial Strains and Cultural Conditionsmentioning
confidence: 99%